2020
DOI: 10.3390/ijerph17041320
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Metabolically Healthy Obesity, Cardiovascular Disease, and All-Cause Mortality Risk in Asia: A Systematic Review and Meta-Analysis

Abstract: We investigated the association among metabolically healthy obesity (MHO), cardiovascular disease (CVD)risk, and all-cause mortality in the Asian population. We searched databases from inception to 16 November, 2019 and pooled data using a random-effects model. Subgroup analysis was conducted according to the following comparison groups: MHNW (without overweight or underweight participants) and MHNO (non-obese, including overweight and underweight participants). Nineteen studies were included. The mean Newcast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…However, in some studies, there was no increased risk for total mortality between participants with MHO and MHNO. [33][34][35] Our included studies also exhibited inconsistent results for cancer risk. The most likely explanation is that the definition of MHO varied widely among studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in some studies, there was no increased risk for total mortality between participants with MHO and MHNO. [33][34][35] Our included studies also exhibited inconsistent results for cancer risk. The most likely explanation is that the definition of MHO varied widely among studies.…”
Section: Discussionmentioning
confidence: 95%
“…To the best of our knowledge, this is the first systematic review and meta-analysis to investigate the relationship between MHO and The health implications of MHO are still debated. The study by Caleyachetty et al 32 with 3.5 million individuals and some metaanalyses 15,17,33 demonstrated that participant with MHO had a higher risk of cardiovascular disease (CVD) than participants with MHNW. However, in some studies, there was no increased risk for total mortality between participants with MHO and MHNO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third paper, "The Association between Metabolically Healthy Obesity, Cardiovascular Disease, and All-Cause Mortality Risk in Asia: A Systematic Review and Meta-Analysis", by Huang et al [3], investigates the association among metabolically healthy obesity (MHO), cardiovascular disease (CVD) risk, and all-cause mortality in the Asian population. Participants with MHO had a significantly lower risk of all-cause mortality than MHNO (non-obese, including overweight and underweight) participants, but a borderline significantly higher risk of all-cause mortality than MHNW (without overweight or underweight) participants.…”
Section: Preventive Medicine and Risk Assessmentmentioning
confidence: 99%
“…These results suggested that abdominal obesity per se is the key role in the progress of subclinical vascular in ammation. Obesity in absence of metabolic risk factors is not entirely benign and MHO population would therefore be expected to have a higher risk of CVD and all-cause mortality than MHNO group (45) The strengths of our study include a twin design, a standard de nition of MetS, adjustment for many available covariates, and various analyses including using strati ed analysis and number of MetS components to test the robustness of the conclusions. However, several potential limitations should be addressed.…”
Section: Within Twin-pair Analysismentioning
confidence: 99%